Islamic finance and banking in Malaysia in 33 questions for beginners - Turkan, Yavuz (Özgür Yayınları Tic. Ltd. Şti., 2022)
The concept of Islamic Finance and Banking has been created and named based on the religion of Islam and clearly is connected to Islam, which was revealed by Allah swt to the whole of humanity as the last religion and provided a structure to manage a social life. This religion, which Allah sent to humanity and whose truths are stated in the Qur’an, was taught to us Muslims under the guidance of our Prophet Muhammad (PBUH). Every Muslim is a real witness to this. The most important and the first of these teachings is faith, as Allah swt has emphasized with the verse “You are the superiors if you’re believers.” (Al-i Imran/139) that believing in himself, his prophet and the truth in his book is the way to success. Therefore, it is essential to act by the principles of Islam for success in both social and economic spheres of life. Likewise, if it is desired to succeed in the banking and finance sectors, the principles of the Islamic religion should be followed. Furthermore, Islamic finance and banking transactions should not be made to conform to material expectations but should be carried out following the truths of the religion of Islam. This principle reveals that sincerity and intention are two important motivations in Islamic finance and banking, coming before numbers and statistical data.